Professional Competences of the Radiographer: A Challenge for the Healthcare System in Bulgaria - Yordanova, Mariana Zhivkova (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
The competence approach applied in the education of radiographers in Bulgaria is a result of the common concept of the educational results already adopted in most developed countries in the form of professional competences viewed as “human capital indicator”. Constant changes in the conditions and the technological development in healthcare lead to the necessity to adopt new competences which correspond to the requirements and needs of the healthcare system. The term professional competence most often is associated with the presence of quality characteristics (knowledge and skills) determining the mastering of a certain profession in order to effectively solve specific tasks and issues in real-life professional environment. Modern concepts of professional competence include not only mastering of the fundaments of the chosen profession but also the possible perspectives for own personal improvement, future specialisation, professionalization and realization.